2015
DOI: 10.1016/j.cmet.2015.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol Protects against Obesity and Metabolic Dysfunction through Activation of a HSF1-PGC1α Transcriptional Axis

Abstract: Altering the balance between energy intake and expenditure is a potential strategy for treating obesity and metabolic syndrome. Nonetheless, despite years of progress in identifying diverse molecular targets, biological-based therapies are limited. Here we demonstrate that heat shock factor 1 (HSF1) regulates energy expenditure through activation of a PGC1α-dependent metabolic program in adipose tissues and muscle. Genetic modulation of HSF1 levels altered white fat remodeling and thermogenesis, and pharmacolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
249
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 270 publications
(276 citation statements)
references
References 58 publications
15
249
2
1
Order By: Relevance
“…Homozygous Pspc1-floxed mice carrying the conditional-ready knockout allele were used for adenovirus-Cre injection studies. For the adenovirus delivery to fat pads, 2 × 10 9 PFU of adenovirus was percutaneously injected into the inguinal fat depot at 8 weeks of age (71). In each mouse, Ad-Cre was injected on one side, and Ad-GFP was injected on the contralateral side.…”
Section: Methodsmentioning
confidence: 99%
“…Homozygous Pspc1-floxed mice carrying the conditional-ready knockout allele were used for adenovirus-Cre injection studies. For the adenovirus delivery to fat pads, 2 × 10 9 PFU of adenovirus was percutaneously injected into the inguinal fat depot at 8 weeks of age (71). In each mouse, Ad-Cre was injected on one side, and Ad-GFP was injected on the contralateral side.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of serum chemistry including cholesterol, triglyceride, and creatine kinase levels were performed by the Department of Laboratory Medicine at the NIH Clinical Center. Glucose tolerance and insulin tolerance tests and liver triglyceride levels were determined as previously described (49,50).…”
Section: Methodsmentioning
confidence: 99%
“…The recent computational study showed that HSE was found in the promoter region of PGC-1α 27) , suggesting transcription of the PGC-1α gene can also be regulated by HSF1. Actually, another recent report has shown that HSF1 positively regulates PGC-1α transcription in adipose tissues and skeletal muscles 28) . Interestingly, although HSR is thought to be the basic preservative and essential process of cell protection, HSF1-dependent PGC-1α transcription depends on tissue type (e.g.…”
Section: Heat Stress Activates Regulatory Factors Of Mitochondrial Bimentioning
confidence: 99%